Use of energy dispersive X-ray fluorescence as screening method to detect oregano adulteration - Sergej Papoci; María Beatriz de la Calle Guntiñas (Current Research in Food Science)
Oregano is frequently adulterated as demonstrated in a recent control plan organised by the European Commission. In this work, the elemental profiles of 282 oregano samples analysed by energy dispersive X-ray fluorescence were used in combination with multivariate analyses to detect adulteration, in particular with olive leaves. The analyses were carried out in the frame of the coordinated control plan on the authenticity of herbs and spices organised by the European Commission. Partial Least Square Discriminant Analyses, allowed the detection of adulterated samples with a sensitivity of 81 %, and a specificity of 92 %; among the adulterated samples PLS-DA allowed the detection of samples that contained olive leaves with a sensitivity of 94 % and a specificity of 92 %. Copper mass fraction is of relevance because it is significantly higher in samples adulterated with olive leaves. The ratio Cu/Zn allowed the identification of adulterated samples with a sensitivity and specificity of 85 % without the need to use modelling techniques. The elemental profile of oregano obtained by EDXRF was also used to authenticate the geographical origin declared in the labels.